God's resistance : mobilizing faith to defend immigrants - Christerson, Brad; Salvatierra, Alexia, 1956-; Romero, Robert Chao, 1972-; Yuen, Nancy Wang, 1976- (New York, New York : New York University Press, 2023)
"This book explores the power of faith in mobilizing resistance to restrictive immigration policies in the US by analyzing the strategies, successes, and failures of faith-based immigrant rights organizations"--
Includes bibliographical references and index.
Description based on print version record.
JSTOR
Keywords: Emigration and immigration -- Religious aspects -- Christianity; Immigrants -- Civil rights; Émigration et immigration -- Aspect religieux -- Christianisme; Emigration and immigration -- Religious aspects -- Christianity; Immigrants -- Civil rights